Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To find [tex]\(\frac{dy}{dx}\)[/tex] for the function [tex]\( y = \frac{(1-x)^{20}}{(1+x)^{25}} \)[/tex], we will need to use the quotient rule. The quotient rule is given as:
[tex]\[ \frac{d}{dx} \left( \frac{u}{v} \right) = \frac{v \frac{du}{dx} - u \frac{dv}{dx}}{v^2} \][/tex]
In this case, we identify [tex]\( u \)[/tex] and [tex]\( v \)[/tex] as follows:
[tex]\[ u = (1 - x)^{20} \][/tex]
[tex]\[ v = (1 + x)^{25} \][/tex]
First, calculate [tex]\(\frac{du}{dx}\)[/tex] and [tex]\(\frac{dv}{dx}\)[/tex]:
[tex]\[ \frac{du}{dx} = 20(1 - x)^{19} \cdot (-1) = -20(1 - x)^{19} \][/tex]
[tex]\[ \frac{dv}{dx} = 25(1 + x)^{24} \cdot 1 = 25(1 + x)^{24} \][/tex]
Now, apply the quotient rule:
[tex]\[ \frac{dy}{dx} = \frac{v \frac{du}{dx} - u \frac{dv}{dx}}{v^2} \][/tex]
Substitute [tex]\( u \)[/tex], [tex]\( v \)[/tex], [tex]\(\frac{du}{dx}\)[/tex], and [tex]\(\frac{dv}{dx}\)[/tex]:
[tex]\[ \frac{dy}{dx} = \frac{(1 + x)^{25} \cdot (-20(1 - x)^{19}) - (1 - x)^{20} \cdot 25(1 + x)^{24}}{(1 + x)^{50}} \][/tex]
Simplify the numerator:
[tex]\[ \frac{dy}{dx} = \frac{-20(1 + x)^{25}(1 - x)^{19} - 25(1 - x)^{20}(1 + x)^{24}}{(1 + x)^{50}} \][/tex]
Factor out common terms from the numerator:
[tex]\[ \frac{dy}{dx} = \frac{(1 - x)^{19}(1 + x)^{24} \left[ -20(1 + x) - 25(1 - x) \right]}{(1 + x)^{50}} \][/tex]
Let's simplify the bracketed expression:
[tex]\[ -20(1 + x) - 25(1 - x) = -20 - 20x - 25 + 25x = -45 + 5x = -45 - 5x \][/tex]
So we get:
[tex]\[ \frac{dy}{dx} = \frac{(1 - x)^{19}(1 + x)^{24}(-45 - 5x)}{(1 + x)^{50}} \][/tex]
Cancel out the common terms:
[tex]\[ \frac{dy}{dx} = \frac{(1 - x)^{19}(1 + x)^{24}(-45 - 5x)}{(1 + x)^{50}} = \frac{(1 - x)^{19}(-45 - 5x)}{(1 + x)^{26}} \][/tex]
Simplifying gives us the final result:
[tex]\[ \frac{dy}{dx} = - \frac{25(1 - x)^{20}}{(1 + x)^{26}} - \frac{20(1 - x)^{19}}{(1 + x)^{25}} \][/tex]
Therefore, the correct form of [tex]\(\frac{dy}{dx}\)[/tex] is:
[tex]\[ \frac{dy}{dx} = - 25 \frac{(1 - x)^{20}}{(1 + x)^{26}} - 20 \frac{(1 - x)^{19}}{(1 + x)^{25}} \][/tex]
This matches our simplified form:
[tex]\[ \frac{dy}{dx} = -25 \frac{(1 - x)^{20}}{(1 + x)^{26}} - 20 \frac{(1 - x)^{19}}{(1 + x)^{25}} \][/tex]
And among the given options, this corresponds to:
(D) [tex]\(-y\left(\frac{20}{1-x}+\frac{25}{1+x}\right)\)[/tex]
Substituting [tex]\(y = \frac{(1 - x)^{20}}{(1 + x)^{25}}\)[/tex] into it leads to [tex]\(\frac{dy}{dx} = -(1 - x)^{20} (20 \frac{(1 - x)^{19}}{(1 + x)^{25}} ) - (25 \frac{(1 + x)^{24}}{(1 + x)^{25}}(1 - x)^{20}) = -25 \frac{(1 - x)^{20}}{(1 + x)^{26}} - 20 \frac{(1 - x)^{19}}{(1 + x)^{25}}\)[/tex]
[tex]\[ \frac{d}{dx} \left( \frac{u}{v} \right) = \frac{v \frac{du}{dx} - u \frac{dv}{dx}}{v^2} \][/tex]
In this case, we identify [tex]\( u \)[/tex] and [tex]\( v \)[/tex] as follows:
[tex]\[ u = (1 - x)^{20} \][/tex]
[tex]\[ v = (1 + x)^{25} \][/tex]
First, calculate [tex]\(\frac{du}{dx}\)[/tex] and [tex]\(\frac{dv}{dx}\)[/tex]:
[tex]\[ \frac{du}{dx} = 20(1 - x)^{19} \cdot (-1) = -20(1 - x)^{19} \][/tex]
[tex]\[ \frac{dv}{dx} = 25(1 + x)^{24} \cdot 1 = 25(1 + x)^{24} \][/tex]
Now, apply the quotient rule:
[tex]\[ \frac{dy}{dx} = \frac{v \frac{du}{dx} - u \frac{dv}{dx}}{v^2} \][/tex]
Substitute [tex]\( u \)[/tex], [tex]\( v \)[/tex], [tex]\(\frac{du}{dx}\)[/tex], and [tex]\(\frac{dv}{dx}\)[/tex]:
[tex]\[ \frac{dy}{dx} = \frac{(1 + x)^{25} \cdot (-20(1 - x)^{19}) - (1 - x)^{20} \cdot 25(1 + x)^{24}}{(1 + x)^{50}} \][/tex]
Simplify the numerator:
[tex]\[ \frac{dy}{dx} = \frac{-20(1 + x)^{25}(1 - x)^{19} - 25(1 - x)^{20}(1 + x)^{24}}{(1 + x)^{50}} \][/tex]
Factor out common terms from the numerator:
[tex]\[ \frac{dy}{dx} = \frac{(1 - x)^{19}(1 + x)^{24} \left[ -20(1 + x) - 25(1 - x) \right]}{(1 + x)^{50}} \][/tex]
Let's simplify the bracketed expression:
[tex]\[ -20(1 + x) - 25(1 - x) = -20 - 20x - 25 + 25x = -45 + 5x = -45 - 5x \][/tex]
So we get:
[tex]\[ \frac{dy}{dx} = \frac{(1 - x)^{19}(1 + x)^{24}(-45 - 5x)}{(1 + x)^{50}} \][/tex]
Cancel out the common terms:
[tex]\[ \frac{dy}{dx} = \frac{(1 - x)^{19}(1 + x)^{24}(-45 - 5x)}{(1 + x)^{50}} = \frac{(1 - x)^{19}(-45 - 5x)}{(1 + x)^{26}} \][/tex]
Simplifying gives us the final result:
[tex]\[ \frac{dy}{dx} = - \frac{25(1 - x)^{20}}{(1 + x)^{26}} - \frac{20(1 - x)^{19}}{(1 + x)^{25}} \][/tex]
Therefore, the correct form of [tex]\(\frac{dy}{dx}\)[/tex] is:
[tex]\[ \frac{dy}{dx} = - 25 \frac{(1 - x)^{20}}{(1 + x)^{26}} - 20 \frac{(1 - x)^{19}}{(1 + x)^{25}} \][/tex]
This matches our simplified form:
[tex]\[ \frac{dy}{dx} = -25 \frac{(1 - x)^{20}}{(1 + x)^{26}} - 20 \frac{(1 - x)^{19}}{(1 + x)^{25}} \][/tex]
And among the given options, this corresponds to:
(D) [tex]\(-y\left(\frac{20}{1-x}+\frac{25}{1+x}\right)\)[/tex]
Substituting [tex]\(y = \frac{(1 - x)^{20}}{(1 + x)^{25}}\)[/tex] into it leads to [tex]\(\frac{dy}{dx} = -(1 - x)^{20} (20 \frac{(1 - x)^{19}}{(1 + x)^{25}} ) - (25 \frac{(1 + x)^{24}}{(1 + x)^{25}}(1 - x)^{20}) = -25 \frac{(1 - x)^{20}}{(1 + x)^{26}} - 20 \frac{(1 - x)^{19}}{(1 + x)^{25}}\)[/tex]
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.